Recent Advances in Multiband Printed Antennas Based on Metamaterial Loading. (22nd October 2012) - Paredes, F.; Zamora, G.; Zufanelli, S.; Herraiz-Martínez, F. J.; Bonache, J.; Martín, F.
Abstract : It is shown that printed antennas loaded with metamaterial resonators can be designed to exhibit multiband functionality. Two different antenna types and metamaterial loading are considered: (i) printed dipoles or monopoles loaded with open complementary split ring resonators (OCSRRs) and (ii) meander line or folded dipole antennas loaded with split ring resonators (SRRs) or spiral resonators (SRs). In the first case, multiband operation is achieved by series connecting one or more OCSRRs within the dipole/monopole. Such resonators force opens at their positions, and by locating them at a quarter wavelength (at the required operating frequencies) from the feeding point, it is possible to achieve multiple radiation bands. In the second case, dual-band functionality is achieved through the perturbation of the antenna characteristics caused by the presence of the metamaterial resonators. This latter strategy is specially suited to achieve conjugate matching between the antenna and the chip in radiofrequency identification (RFID) tags at two of the regulated UHF-RFID bands.